2020
DOI: 10.3389/fgwh.2020.00004
|View full text |Cite
|
Sign up to set email alerts
|

Gender-Based Violence During COVID-19 Pandemic: A Mini-Review

Abstract: Purpose: Quarantine is necessary to reduce the community spread of the Coronavirus disease, but it also has serious psychological and socially disruptive consequences. This is known as the quarantine paradox that also includes a surge in the cases of genderbased violence. However, there exists a clear gap of rigorous literature exploring the issue. Hence, the current paper attempts to understand gender-based violence as an aspect of the COVID-19 lockdown. It reviews the pattern of rise in gender violence cases… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

15
213
0
9

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 243 publications
(237 citation statements)
references
References 40 publications
15
213
0
9
Order By: Relevance
“…SGBV is exacerbated during crisis situations because of heightened gender inequality and financial pressures (4), as well as difficulties in accessing relevant medical and legal services (5). COVID-19 has further intensified SGBV due to lockdown measures, effectively trapping victims in their homes with potential abusers [for a review of GBV during COVID-19, see (4)].…”
Section: Introductionmentioning
confidence: 99%
“…SGBV is exacerbated during crisis situations because of heightened gender inequality and financial pressures (4), as well as difficulties in accessing relevant medical and legal services (5). COVID-19 has further intensified SGBV due to lockdown measures, effectively trapping victims in their homes with potential abusers [for a review of GBV during COVID-19, see (4)].…”
Section: Introductionmentioning
confidence: 99%
“…The risk factors that are identified as attributive to the surge in domestic violence against women and children during the pandemic include economic insecurity and poor coping strategies that include alcohol consumption and substance abuse on the part of men (Human Rights Watch, 2020). Indeed, it has been reported that increasing male unemployment is associated with increasing interpersonal violence against women (Bhalotra et al as cited in Mittal & Singh, 2020). Schneider et al (as cited in Mittal & Singh, 2020) suggest that such an outcome could be the male backlash resulting from the feelings of emasculation and inadequacy at not being able to fulfil the requirements of conventional manhood.…”
Section: The Impact: Positives and Negativesmentioning
confidence: 99%
“…Indeed, it has been reported that increasing male unemployment is associated with increasing interpersonal violence against women (Bhalotra et al as cited in Mittal & Singh, 2020). Schneider et al (as cited in Mittal & Singh, 2020) suggest that such an outcome could be the male backlash resulting from the feelings of emasculation and inadequacy at not being able to fulfil the requirements of conventional manhood. Further, the financial impact of COVID-19 has been also identified as a factor that plays a major role in the break-up of families and couples, especially given its detrimental psychological impact on men, ‘more so than women still base their self-worth on their ability to provide economic security for their family’ (Savage, 2020).…”
Section: The Impact: Positives and Negativesmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, lockdowns and curfews mean that people have to remain VIOLENCE DURING COVID-19 IN KENYA indoors with abusers and are unable to access outside assistance because police and vital services are unavailable, and abusers can act with impunity. 22, . 23 More research on SGBV during times of compounding crises is needed, however.…”
Section: During the Covid-19 Pandemic In Kenyamentioning
confidence: 99%